Dermatologic aspects of bed bug epidemic: an atlas of differential diagnosis - Fésűs, Luca; Jobbágy, Antal; Kiss, Norbert; Horváth, Eszter; Avci, Pinar; Lukács, Andrea; Mayer, Katalin; Bergler-Czop, Beata; Wikonkál, Norbert; Bánvölgyi, András (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Bed bug infestation rate has gone through an unforeseen increase in the past decades worldwide. Their resurgence is a consequence of numerous factors, including growing population density, increased international travel and the spread of insecticide resistance. Bed bug infestation is often revealed by skin symptoms appearing after their bite in sensitive patients. Medical professionals encountering patients with bed bug bites have responsibility for recognizing the condition and for instructing patients about the necessary measures for eradication. Setting the correct diagnosis, however, is not unequivocal as several skin diseases with autoimmune, immune-mediated aetiology or other arthropod stings and bites may present with similar symptoms. In this review we provide a differential diagnostic guide and an atlas of clinical pictures assigned to the diagnoses. We highlight those dermatological findings where the possibility of bed bug bite arises and identify key elements that help in the differentiation so as to avoid unnecessary diagnostic tests and force early start of extermination.